2012
DOI: 10.1186/1471-2458-12-1077
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for return to work among sickness certified patients in general practice

Abstract: BackgroundLong-term sickness absence is one of the main risk factors for permanent exit out of the labour market. Early identification of the condition is essential to facilitate return to work. The aim of this study was to analyse possible determinants of return to work and their relative impact.MethodsAll 943 subjects aged 18 to 63 years, sickness certified at a Primary Health Care Centre in Sweden from 1 January until 31 August 2004, were followed up for three years. Baseline information on sex, age, sick l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…Even though women have higher sickness absence, this seems to be restricted to short-term sick leave [24] rather than long-term sick leave [3]. In the Swedish context, a recent study found no association between female gender and RTW [6]. Hence, even though the onset of sick leave may differ between women and men, the same ailment seems to hamper RTW to the same degree for both women and men.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Even though women have higher sickness absence, this seems to be restricted to short-term sick leave [24] rather than long-term sick leave [3]. In the Swedish context, a recent study found no association between female gender and RTW [6]. Hence, even though the onset of sick leave may differ between women and men, the same ailment seems to hamper RTW to the same degree for both women and men.…”
Section: Discussionmentioning
confidence: 92%
“…Adjustment was made for available variables previously reported to be potentially associated with sick leave, in general [19], or RTW, in particular [2,3,6]. There is a risk of over adjustment but the size of the available data reduces the risk of type II errors.…”
Section: Confoundersmentioning
confidence: 99%
See 2 more Smart Citations
“…During 2010-2012, 41 000 individuals in Sweden lost their sick leave benefits, not because their health had improved, but because of the newly introduced time restrictions. From a medical rehabilitation point of view, it is of interest to investigate different aspects of health in this group as the various health situations are major determinants for returning to work (Von Celsing et al, 2012).…”
Section: Introductionmentioning
confidence: 99%